Association between head and face injuries and helmet use and hospitalization costs of motorcycle accidents in Azahra Hospital in Isfahan in 2010 - Zahra Seiedmoalemi; Azam Dadkhah (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Road accidents, with motorcycle accidents comprising a major fraction of them, are the second most important cause of death in Iran. This study aimed to evaluate the frequency of head and face injuries in motorcyclists who had an accident and to find out relationship between helmet use and frequency of these injuries and hospitalization costs of these accidents. Materials and Methods: Data in this retrospective descriptive-analytical study was collected from "Form 92", a registration form of motorcyclists who had accidents and were hospitalised in the Azahra Hospital in 2010, including hospitalization period, treatment costs, severity of injuries, and time of the accident (n = 1626). Of the injured motorcyclists registered in Form 92 during the last three months of the year, 125 cases were randomly selected and interviewed by phone in relation to wearing a helmet during the accident. Data was analyzed by descreptive tests and Phi & Cramer's correlation coefficient using SPSS 11.5 (α = 0.05).Results: Accidents by motorcycle comprised 31% of all the registered motor vehicle accidents. The frequency of motocycle accidents was higher in October and among 21-25 year-olds. The mean period of hospitalization was 4.3 days and the mean of hospital costs was about 9,000,000 Rials. The frequency of head and face injuries was 51% among all the injured motorcyclists, with 22% among those wearing a crash helmet and 78% among those not wearing a crash helmet (r = 0.267, p value = 0.009). A total of 35% of motorcyclists reported wearing crash helmets.Conclusion: Based on the results of the present study, motorcycle accidents impose a lot of costs on peple and the community. Use of a crash helmet can significantly reduce the frequency of head and face injuries more than three folds. Key words: Accident, Cost control, Crash helmet, Traffic.